Early gastric cancer mimicking advanced gastric cancer. - Kitamura, K. (Nature Publishing Group, 1997)
The clinicopathological features of 37 early gastric cancers mimicking advanced gastric cancer were reviewed retrospectively, and were compared with 596 other early gastric cancers and 126 mp gastric cancers, defined as gastric cancer invading the muscularis propria of the stomach. A greater tumour size (P < 0.005), submucosal invasion (P < 0.005), lymph node and lymph vessel invasion (P < 0.005) and vascular invasion (P < 0.025) were found more frequently in early gastric cancers mimicking advanced gastric cancers than in other early gastric cancers. There were no significant differences in the clinicopathological findings between early gastric cancers mimicking advanced gastric cancers and mp gastric cancers. Patients with early gastric cancers mimicking advanced gastric cancers showed a lower survival rate than patients with other early gastric cancers, but a higher survival than those with mp gastric cancers. The macroscopic appearance of an advanced gastric cancer was an indicator of massive submucosal invasion and lymph node metastasis in early gastric cancer. As early gastric cancers mimicking advanced gastric cancers showed similar clinicopathological findings to mp gastric cancers, these cancers should be treated as mp gastric cancers. IMAGES: